The effect of intermittent sequential pneumatic compression on recovery between exercise bouts in well-trained triathletes - O'Donnell, S.; Driller, M. W. (Journal of Science and Cycling, 2015)
To evaluate the effectiveness of one method of intermittent sequential pneumatic compression (ISPC) on the recovery between exercise bouts in well-trained triathletes. Ten well-trained male triathletes (mean ± SD; age = 29 ± 9 y, mass = 72kg ± 11kg) completed a familiarization trial and two experimental trials in a randomized, cross-over design. Participants performed a 40-minute high-intensity interval session on a cycle ergometer, followed by a 30- minute recovery period where participants completed either passive recovery (CON) or ISPC recovery. Following the recovery period, participants performed a 5km run time-trial on a treadmill (5kmTT). Blood lactate concentration, 5kmTT time and total quality recovery (TQR) were used to examine the effect of ISPC compared to CON. The 5kmTT resulted in a non-significant difference (P = 0.31, ES = 0.07) between groups of 8.2 ± 23.7 seconds in favour of the ISPC trial (ISPC; 1189.7 ± 94.9 and CON; 1197.9 ± 101.9). There were no significant differences between trials for blood lactate concentrations or TQR. The current study reports that ISPC was not effective in improving recovery between a cycling and running bout in well-trained triathletes.